Management of HCV Treatment-related Side-effects, Toxicity, and Drug-interactions - Kawamoto, PharmD, Jenna K.; Smith, PharmD, Jason P.; Han, MD, AGAF, Steven-Huy B. (North American Journal of Medicine and Science, 2014)
Direct-acting antiviral (DAA) protease inhibitors, boceprevir (BOC) and telaprevir (TVR) were FDA-approved in 2011 to be used in combination with pegylated interferon (peg-IFN) and ribavirin for the treatment of chronic hepatitis C virus infection (HCV) genotype 1. The addition of these new DAAs increased cure rates but also increased rates of adverse events and drug interactions. This review will evaluate HCV treatment-related side-effects, toxicity, and drug-interactions and management. Understanding and identifying adverse events and drug interactions will help enable the provider to minimize treatment discontinuation, prevent serious adverse events, and optimize treatment for patients.